2013
DOI: 10.1007/s11999-012-2566-2
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity as a Risk Factor for Lateral Condyle Fractures Over Supracondylar Humerus Fractures

Abstract: Background Obese children reportedly have an increased risk of sustaining musculoskeletal injuries compared with their normal-weight peers. Obese children are at greater risk for sustaining fractures of the forearm, particularly from low-energy mechanisms. Furthermore, obesity is a risk factor for sustaining an extremity fracture requiring surgery. However, it is unclear what role obesity plays in fractures about the distal humerus. Questions/purposes We therefore asked whether (1) children who sustain lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
(44 reference statements)
0
30
1
1
Order By: Relevance
“…However, accelerated skeletal growth and greater bone size may not translate into reduced fracture risk. In fact, two recent studies reviewing the medical records of patients aged 2 to 19 yr showed that overweight and obese children had an increased odds ratio of fracture, with the association strongest in the 6-11 year-old age group (5, 6). Gender may affect the association between obesity and bone outcomes.…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…However, accelerated skeletal growth and greater bone size may not translate into reduced fracture risk. In fact, two recent studies reviewing the medical records of patients aged 2 to 19 yr showed that overweight and obese children had an increased odds ratio of fracture, with the association strongest in the 6-11 year-old age group (5, 6). Gender may affect the association between obesity and bone outcomes.…”
Section: Children and Adolescentsmentioning
confidence: 99%
“…These differences in the mean values of the perimeters can be explained by the fact that the sessions of "Circuit Training", held in sports, were performed with progressive intensity 60-85% of maximum heart rate, according to the American College of Sports Medicine [13], where more emphasis was given to the aerobic phase. Olson et al [22], Stanforth et al [23], Fornari et al [24], and Conti [25] explain that the exercise intensity, the duration of the aerobic phase are crucial to promote changes in the cardiovascular level and caloric expenditure.…”
Section: It Was Found Through Thementioning
confidence: 99%
“…Childhood obesity is an ongoing epidemic in the United States [4,5]. The most recent data from the US indicate that 16.9% of children and adolescents are obese, defined as a body mass index (BMI) for age >95th percentile [6,7] and there is evidence that the prevalence of obesity among children will reach 30% by 2030 [8]. Childhood obesity is a risk factor for greater morbidity later in life, including diabetes, coronary artery disease and increased mortality [4,5,9,10].…”
mentioning
confidence: 99%